Microbiology and immunology of fish larvae. (27th May 2013) - Vadstein, Olav; Bergh, Øivind; Gatesoupe, François‐Joel; Galindo‐Villegas, Jorge; Mulero, Victoriano; Picchietti, Simona; Scapigliati, Giuseppe; Makridis, Pavlos; Olsen, Yngvar; Dierckens, Kristof; Defoirdt, Tom; Boon, Nico; et al.
Abstract: For most marine aquaculture species, one of the main bottlenecks is the stable production of high quality juveniles. The high and unpredictable mortality in the first weeks after hatching of marine fish larvae remains a challenging problem that needs to be solved. The severity of the problem differs between species, but cannot be considered adequately solved for any species. Both scientific evidence and experience in hatcheries for a variety of fish, shrimp and shellfish species are accumulating as support for the hypothesis that detrimental fish–microbe interactions are the cause of these problems. Host–microbe interactions in reared fish are still poorly understood, except for a few pathogens, and empirical data of the quality required to test this hypothesis, are lacking. This article provides an overview on the current knowledge of the microbial environment of fish larvae, including methodological aspects to characterize the microbial community (both using culture‐dependent and culture‐independent methods). Further, the current knowledge of the immunology of fish larvae is reviewed, including recent advances in the understanding of toll‐like receptors, inflammatory cytokines, mast cells and piscidins, and the ontogeny of the adaptive immune system. Finally, we provide an overview of the state of the art with respect to steering of microbial communities associated with fish larvae – both steering of community composition and of its activity (e.g. by quorum sensing interference).